(untitled) (Eurasian Journal of Ecology, 2016)
The article discusses some aspects of the cultivation of valuable chickpea leguminous crops in the dry zone of Priuralie. Seeds treatment by microbic agents and soil application of mineral, nitrogen and phosphorous fertilizers improve the nutritional regime of the soil and nitrogenase activity of chickpea.